Pengaruh Pemangku Kepentingan Dan Pemegang Saham Terhadap Kualitas Laporan Berkelanjutan - Andrean Yosua; Herlin Tundjung (Fakultas Ekonomi, Universitas Tarumanagara, 2022)
The objective of this study is to analize the effect of environmental sensitive industries, employee pressure, and concentrated ownership on the quality of sustainability reporting of companies listed in the Indonesian Stock Exchange in the period of 2015 to 2019 with assurance statement as moderating variable. This study uses 16 stand–alone sustainability reports and multiple liniar regression as its statistical technique. The results of this study indicates that environmental sensitive industries and employee pressure positively and significantly affect the quality of sustainability reporting while concentrated ownership doesn't significantly affect the quality of sustainability reporting. This study also indicates that assurance statement strengthens the effect of environmentally sensitive industries towards the quality of sustainability reporting.